Increases the Competence of Sports Science-Based Karate Trainers in Facing the Demands of Competition Activities for FORKI Trainers in Padang Pariaman Regency - Septri; Anggun Permata Sari; Hadi Pery Fajri; Sonya Nelson (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2024)
The partner in this service is FORKI Padang Pariaman, targeting trainers and assistant trainers in Padang Pariaman Regency. Mitra's problems are: 1) the low level of understanding of karate trainers regarding the basics of coaching science. Most karate trainers rely on their previous experience as athletes in training, so the training methods used are still classical and traditional. Apart from that, the karate trainers in Padang Pariaman Regency are still dominated by trainers who do not have an educational background in sports. The lack of human resources for trainers who have sports scientific competence will certainly affect the development of sports science and technology (IPTEK)-based coaching. 2) The performance of Karate athletes in Padang Pariaman Regency is not yet optimal and it is still very difficult to compete with other regions both at the internal and multi-event levels. The implementation method for this service is Training of Trainers (TOT) by providing material through lectures, then followed by direct practice. The result of mentoring is an increase in the trainer's competency regarding the basics of coaching science and training program planning.